Early diaphragm dysfunction assessed by ultrasonography after cardiac surgery: a retrospective cohort study - Huai, Hongbo; Ge, Min; Zhao, Zhigang; Xiong, Ping; Hong, Wenjun; Jiang, Zhongli; Wang, Jianming (Frontiers in Cardiovascular Medicine, 2024)
Objective: Approximately 10-70% of patients may develop diaphragmatic dysfunction after cardiac surgery, which may lead to delayed weaning from mechanical ventilation, increased ICU stays, postoperative hospitalization stays, and respiratory complications. However, its impact on prognosis and risk factors remain controversy. Therefore, we conducted a retrospective cohort study in which we evaluated diaphragmatic dysfunction in patients who underwent cardiac surgery via bedside diaphragm ultrasound to investigate its prognosis and possible risk factors. Methods: Data from the electronic medical records system included case records and ultrasound images of the diaphragm for 177 consecutive patients admitted to the ICU following cardiac thoracotomy surgeries performed between June and September 2020. Diaphragmatic dysfunction was defined as a diaphragmatic excursion of less than 9 mm in women and less than 10 mm in men at rest, with an average thickening fraction of less than 20%. SPSS 25.0 software was used to analyse the relationships between patients' general information, intraoperative and postoperative factors and diaphragmatic dysfunction, as well as the impact on patients' hospitalization days, mechanical ventilation time and respiratory system complications. Results: The incidence of early postoperative diaphragmatic dysfunction after cardiac surgery was 40.7%. Patients with diaphragmatic insufficiency were more likely to sequentially use noninvasive ventilation within 24 hours after weaning off mechanical ventilation (3.8% vs. 12.5%, P=0.029) and to require more oxygen support (23.8% vs. 40.3%, P=0.019). Although there was no significant difference, the diaphragmatic dysfunction group tended to have longer ICU stays and postoperative hospital stays than did the normal diaphragmatic function group (P=0.119, P=0.073). Univariate and multivariate logistic regression analyses both revealed that chest tube drainage placed during surgery accompanied by bloody drainage fluid was an independent risk factor for diaphragmatic dysfunction (univariate analysis: 95% CI: 1.126-4.137, P=0.021; multivariate analysis: 95% CI: 1.036-3.897, P=0.039). Conclusion: Eearly diaphragmatic dysfunction after cardiac surgery increased the proportion of patients who underwent sequential noninvasive ventilation after weaning from mechanical ventilation and who required more oxygen. Chest tube drainage placed during surgery accompanied by bloody drainage fluid was an independent risk factor for diaphragmatic dysfunction, providing evidence-based guidance for respiratory rehabilitation after cardiac surgery.